Une poursuite d'études accompagnée - Sophie Orange (Les éditions de la Maison des sciences de l'Homme, 2009)
Higher Technicians Sections (STS) allow underclass families to stay into the educational system after Baccalauréat thanks to a new distribution of roles for school, students and their parents within higher education. They lead parents to help reasonably their children in their study choices, while building a partnership between parents and school. School perseveres at making parents aware of their responsibilities during the whole curriculum, at controlling regular attendance classe. It extends by two years after the Baccalauréat their role of students' parents. This compromise has effects on STS students as they are given a school and social in-between status : not anymore secondary school pupils, but not students yet.